2002
DOI: 10.1242/jeb.205.2.211
|View full text |Cite
|
Sign up to set email alerts
|

In vivo oocyte hydration in Atlantic halibut (Hippoglossus hippoglossus); proteolytic liberation of free amino acids, and ion transport, are driving forces for osmotic water influx

Abstract: SUMMARY The in vivo swelling and hydration of maturing oocytes of Atlantic halibut Hippoglossus hippoglossus were studied in order to characterise the osmotic mechanism underlying oocyte hydration in oviparous marine teleosts that spawn pelagic eggs. Sequential biopsies from two females, spanning four hydration cycles, were examined by osmometry, solute analysis and electrophoresis of dissected hydrating oocytes and ovulated eggs. The hydration cycle of the biopsied halibuts lasted 33–54 h. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(16 citation statements)
references
References 65 publications
2
14
0
Order By: Relevance
“…A detailed characterization of Gulf of St. Lawrence Atlantic halibut spawning behavior from the same recovered PSATs revealed that Atlantic halibut engage in distinct rapid, 3-202 minute (median of 21 min) rises off the seafloor of an amplitude ranging between 25 and 284 m (Marshall 2020). Supporting earlier evidence for batch spawning (Methven et al 1992), female Atlantic halibut performed between 5 and 13 spawning rises (median of 7) with a median between-rise interval of 3.15 days (Marshall 2020), which corresponds to the time necessary for female Atlantic halibut to hydrate sequential egg batches (Finn et al 2002).…”
Section: Spawning Behaviorsupporting
confidence: 68%
“…A detailed characterization of Gulf of St. Lawrence Atlantic halibut spawning behavior from the same recovered PSATs revealed that Atlantic halibut engage in distinct rapid, 3-202 minute (median of 21 min) rises off the seafloor of an amplitude ranging between 25 and 284 m (Marshall 2020). Supporting earlier evidence for batch spawning (Methven et al 1992), female Atlantic halibut performed between 5 and 13 spawning rises (median of 7) with a median between-rise interval of 3.15 days (Marshall 2020), which corresponds to the time necessary for female Atlantic halibut to hydrate sequential egg batches (Finn et al 2002).…”
Section: Spawning Behaviorsupporting
confidence: 68%
“…Fulton (1897) noted that pelagic eggs of teleosts increase in size during the maturation phase and surmised that this increase in water content affected egg buoyancy. Additional studies have confirmed that pelagic eggs take on more water than benthic eggs of marine teleosts (Finn et al ., 2002a; Matsubara & Koya, 1997) and thus show a greater increase in size. The influx of water is primarily driven by high concentrations of free amino acids (Craik & Harvey, 1987; Finn et al ., 2002b, 2002a; Fyhn et al ., 1999; Thorsen & Fyhn, 1996), and phosphate and other ions (Craik & Harvey, 1986, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies have confirmed that pelagic eggs take on more water than benthic eggs of marine teleosts (Finn et al ., 2002a; Matsubara & Koya, 1997) and thus show a greater increase in size. The influx of water is primarily driven by high concentrations of free amino acids (Craik & Harvey, 1987; Finn et al ., 2002b, 2002a; Fyhn et al ., 1999; Thorsen & Fyhn, 1996), and phosphate and other ions (Craik & Harvey, 1986, 1987). The increase in size in the paddlefish eggs infected with P. hydriforme is comparable to those of pelagic eggs in marine teleosts.…”
Section: Discussionmentioning
confidence: 99%
“…Although marine pelagic eggs achieve hydration in the ovary in the same way [37,40,41], the effect of the T-FAA content on the osmolality of marine pelagic eggs is considerably greater than that of freshwater semibuoyant eggs. This result indicates that fishes have likely evolved divergent metabolic pathways under different salinity regimes.…”
Section: Biochemical Changes For Hydration In Freshwater Fishmentioning
confidence: 96%